Pricing for Profit : How to Command Higher Prices for your Products and Services - Dale Furtwengler (USA AMACOM, 2010)
Many small business owners are trapped by industry pricing and market misconceptions, when they could be compensated for the true value of the product or service being offered. The low price they feel compelled to offer limits their ability to generate profits which, in turn, slows their response to changing customer needs. The good news is that a business can command almost any price it chooses by focusing on the value--not the cost--to the customer. Pricing for Profit shows businesspeople how to break out of the stranglehold of industry pricing and charge more for their wares (regardless of the competition) without alienating their customers. Readers will learn how to: - Quantify the value of their products or services - Distinguish between price buyers and value buyers - Bundle their offerings for competitive advantage and increased customer value - Craft a powerful marketing message that communicates value - Generate more unit sales and close more sales overall, at higher prices - Make more money with less effort Filled with easy-to-use formulas, sample scripts, clear examples, instructive exercises, and more, this accessible and practical guide is a must-read for businesspeople who want to be well-paid for the value they provide.
Keywords: Marketing; Nonfiction; Pricing; Business